2021
DOI: 10.3390/ijerph18189503
|View full text |Cite
|
Sign up to set email alerts
|

Economic Policy Uncertainty, Environmental Regulation, and Green Innovation—An Empirical Study Based on Chinese High-Tech Enterprises

Abstract: As the continuous changes in environmental regulations have a non-negligible impact on the innovation activities of micro subjects, and economic policy uncertainty has become one of the important influencing factors to be considered in the development of enterprises. Therefore, based on the panel data of Chinese high-tech enterprises from 2012–2017, this paper explores the impact of heterogeneous environmental regulations on firms’ green innovation from the perspective of economic policy uncertainty as a moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…Lanoie took the Canadian manufacturing industry as an example and found that the long-term dynamic impact of environmental regulation on productivity was positive, but the short-term impact was negative [ 21 ]. According to Zhu et al, there is a relationship between market-incentive environmental regulation and green innovation in high-tech enterprises [ 28 ]. Some also hold the view that environmental regulation does not affect green innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Lanoie took the Canadian manufacturing industry as an example and found that the long-term dynamic impact of environmental regulation on productivity was positive, but the short-term impact was negative [ 21 ]. According to Zhu et al, there is a relationship between market-incentive environmental regulation and green innovation in high-tech enterprises [ 28 ]. Some also hold the view that environmental regulation does not affect green innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Referring to the practice of Zhu et al [ 28 ] and others, this study selects the number of green patent authorizations to measure green innovation (GIA) because green patent applications are not necessarily authorized. According to the definition of China’s Patent Law, invention patents focus on the technological innovation of products and methods, whereas utility models prefer the practical application of product shape and structure, which shows that invention patents are more effective in improving the level of technological innovation.…”
Section: Sample Sources and Empirical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 There is no doubt that hightech enterprises play an essential role in the Chinese economy (Liu et al, 2020). To furtherly promote economic transformation and development, the Chinese government has formulated a series of preferential measures to encourage enterprises to declare high-tech enterprises (Zhu Y. et al, 2021). Chinese high-tech enterprises refer to resident enterprises registered in China (excluding Hong Kong, Macao, and Taiwan) that continue to carry out research and development and transformation of technological innovations in the "high-tech industry" (Chen, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the environmental carrying capacity of the YREB is very limited, and the economic development mode with high energy consumption, high pollution, and high emissions cause the continuous deterioration of the environmental situation. As a result, the Chinese government has to implement strict environmental regulation policies to curb environmental deterioration [3]. What influences will environmental regulation have on the economic development of the YREB?…”
Section: Introductionmentioning
confidence: 99%